INNOVATION IMPORT SUBSTITUTION AS AN IMPERATIVE OF SUSTAINABLE ECONOMIC DEVELOPMENT OF THE RUSSIAN FEDERATION - Cherkesova, Elvira; Mironova, Daria; Vilisova, Maria; Ryabocon, Natalya; Popova, Tatyana (Revista Inclusiones, 2020)
The article examines the essence and role of import substitution as an efficient strategy of the longterm development of the Russian economy in the context of sanction pressure of the Western countries. The authors chose the institutional peculiarities of organization of process of the rational import substitution as the research subject. In the article the authors sorted out objective factors confirming the economic reasonability of the import substitution, and potential threats accompanying its implementation. The authors systematized assessment-analytical tools for researching a level of the country’s dependence on imports by separate commodity groups in some branches and spheres of the activities, and they specified an algorithm of methods of assessing a demand for the import substitution at an industrial enterprise. The authors offered institutional conditional and determinants, which can favor the efficient implementation of the import substitution policy in the Russian Federation.